Exploring the role of international rankings in the development of institutional public relations strategies - Ramadhan, Hamzah; Sarwono, Dian Ayuria (Universitas Negeri Yogyakarta, 2024)
The study uncovered that educational institutions cannot exclusively rely on their international ranking achievements to maintain their legitimacy. Universities must prioritize strategic communication to enhance their competitive position in the global education market. The study employed a mixed-methods approach, encompassing in-depth interviews and focus group discussions with a cohort of 37 first-year students attending a private institution. The study revealed that students' decision-making process in selecting a private university was intricate and involved multiple aspects. In addition to rankings, students also considered variables such as parental influence, networking possibilities, and the level of facilities and support services provided by the university. Consequently, colleges should prioritize not only their rankings but also other marketing tactics to recruit students. Although university rankings like QS and Times Higher Education significantly influence the perception of institutions in terms of quality and prestige, it is advisable to adopt a more balanced approach. Access to information via digital platforms, such as websites and social media, has played a critical role in demonstrating the program's and university's reliability. Public relations initiatives, however, have focused on highlighting the excellence of education and the societal obligations of universities in the fiercely competitive higher education sector.